Environmental regulation and synergistic effects of PM2.5 control in China. (20th February 2022) - Li, Xinyao; Xue, Wenhao; Wang, Kai; Che, Yunfei; Wei, Jing
Abstract: In recent years, haze pollution has been widespread across China, and the intensity of environmental regulation has been continuously strengthened. Differences in regional environmental regulation intensity brought about the spillover effect of air pollution. In this study, we analyze the spatiotemporal variation trends and distribution of provincial environmental regulation in China from 2004 to 2017. Considering the spatiotemporal lag effect of haze pollution, the dynamic spatial Durbin model was employed to study the spatial impact of environmental regulation tools of different pollutants on PM2.5 (fine particulate matter with aerodynamic diameters ≤2.5 μm). We found that PM2.5 is significantly negatively related to the environmental regulation intensity and synergy, showing a lag effect of 1–2 periods. The environmental regulation level is high in Eastern China but low in western areas, however, most regions lack an important understanding of environmental regulation. Overall, only 19.8%, 23.0%, and 28.1% of the regions exceeded the average level of the environmental regulation intensity of SO2, smoke/dust (SD), and NOX, respectively. PM2.5 yields a spatial spillover effect and is also negatively correlated to the environmental regulation tools of various pollutants. For every 1% increase in the environmental regulation intensity (synergy) of above three pollutants, PM2.5 will be significantly (p < 0.05) reduced by 0.02% (0.04%), 0.05% (0.10%) and 0.04% (0.08%), respectively. Inter-regional collaboration has a profound and long-term impact on PM2.5 and is conducive to improving the efficiency of environmental governance.